(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
This study assesses stakeholders’ perspective on poverty reduction in slum areas of Kathmandu metropolitan city through a survey of 120 randomly selected slum dwellers. Using self-administered structured questionnaires, it examines socio-economic backgrounds, health, security, community participation, and program effectiveness. Quantitative analysis with SPSS and Excel provides insights into the impact of current poverty alleviation efforts. The study found that slum residents experience poverty as an interlocking crisis of social, economic, and spatial deprivations. Demographically, a working-age population remains trapped in informal labor with alarmingly low educational attainment. Chronic food insecurity affects 96.7 percent of households, while healthcare services and public infrastructure remain critically inadequate. Despite Nepal’s progressive policy landscape, including constitutional mandates and the Local Government Operation Act (2017), a cavernous implementation gap exists between policy intent and ground-level reality. Government and NGO programs are rated as ineffective, characterized by fragmented, short-term interventions lacking community engagement. The study concludes that stakeholders’ effort have helped with service delivery and some economic support to the slum dwellers. However, sustainable poverty reduction requires integrated, participatory approaches that address root causes, strengthen local governance accountability, and align strategies with human rights principles. Recommendations include increased investment in education, healthcare, livelihood creation, and stronger coordination between local governments, NGOs, and communities to ensure inclusive and equitable development.